Answer:
a) -27 a³ b⁶
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given ( -3 ab² )³
By using (ab )ⁿ = aⁿ bⁿ
( -3 ab² )³ = (-3)³ a³ (b²)³
Again , using formula ![(a^{m} )^{n} = a^{mn}](https://tex.z-dn.net/?f=%28a%5E%7Bm%7D%20%29%5E%7Bn%7D%20%3D%20a%5E%7Bmn%7D)
= -27 a³ b⁶
R * p = -37.8
Solve for either R or p.
R = -37.8/p
Now plug into R + p = 13.5
-37.8/p + p = 13.5
Solve for p.
After finding p, plug your p-value into either R + p or R*p to find R.
Take it from here.
Answer:
x=3/2,1
Step-by-step explanation:Given
(3x-2)ˆ5-(3x-2)ˆ2=0
(3x-2)ˆ3(3x-2)ˆ2-(3x-2)ˆ2=0
(3x-2)ˆ2{(3x-2)ˆ3-1}=0
(3x-2)ˆ2=0 Or (3x-2)ˆ3-1=0
3x-2=0 Or(3x-2)ˆ3=1
x=3/2 Or 3x-2=1, x=1
You would call them <span>Ice Queen Clones</span>
Answer:
why wont u just go to quizlet for the answer of look it up on calculator soup it is a great place for those kinds of answers
Step-by-step explanation: